Pharmacological potential of Withania somnifera (L.) Dunal and Tinospora cordifolia (Willd.) Miers on the experimental models of COVID-19, T cell differentiation, and neutrophil functions - Zaigham Abbas Rizvi; Zaigham Abbas Rizvi; Prabhakar Babele; Upasna Madan; Upasna Madan; Srikanth Sadhu; Srikanth Sadhu; Manas Ranjan Tripathy; Manas Ranjan Tripathy; Sandeep Goswami; Sandeep Goswami; Shailendra Mani; et al. (Frontiers in Immunology)
Cytokine release syndrome (CRS) due to severe acute respiratory coronavirus-2 (SARS-CoV-2) infection leads to life-threatening pneumonia which has been associated with coronavirus disease (COVID-19) pathologies. Centuries-old Asian traditional medicines such as Withania somnifera (L.) Dunal (WS) and Tinospora cordifolia (Willd.) Miers (TC) possess potent immunomodulatory effects and were used by the AYUSH ministry, in India during the COVID-19 pandemic. In the present study, we investigated WS and TC’s anti-viral and immunomodulatory efficacy at the human equivalent doses using suitable in vitro and in vivo models. While both WS and TC showed immuno-modulatory potential, WS showed robust protection against loss in body weight, viral load, and pulmonary pathology in the hamster model of SARS-CoV2. In vitro pretreatment of mice and human neutrophils with WS and TC had no adverse effect on PMA, calcium ionophore, and TRLM-induced ROS generation, phagocytosis, bactericidal activity, and NETs formation. Interestingly, WS significantly suppressed the pro-inflammatory cytokines-induced Th1, Th2, and Th17 differentiation. We also used hACE2 transgenic mice to further investigate the efficacy of WS against acute SARS-CoV2 infection. Prophylactic treatment of WS in the hACE2 mice model showed significant protection against body weight loss, inflammation, and the lung viral load. The results obtained indicate that WS promoted the immunosuppressive environment in the hamster and hACE2 transgenic mice models and limited the worsening of the disease by reducing inflammation, suggesting that WS might be useful against other acute viral infections. The present study thus provides pre-clinical efficacy data to demonstrate a robust protective effect of WS against COVID-19 through its broader immunomodulatory activity